2021
DOI: 10.1029/2020ef001788
|View full text |Cite
|
Sign up to set email alerts
|

Potential for Electric Vehicle Adoption to Mitigate Extreme Air Quality Events in China

Abstract: Electric vehicle (EV) adoption promises potential air pollutant and greenhouse gas (GHG) reduction co‐benefits. As such, China has aggressively incentivized EV adoption, however much remains unknown with regard to EVs’ mitigation potential, including optimal vehicle type prioritization, power generation contingencies, effects of Clean Air regulations, and the ability of EVs to reduce acute impacts of extreme air quality events. Here, we present a suite of scenarios with a chemistry transport model that assess … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…China has already implemented various strategies, including the 11th Five Year Plan (2006–2010) as well as a number of pollution reduction and energy conservation measures since the 2008 Beijing Olympic Games, such as improving coal combustion efficiency, shutting down factories, and developing new fuels (Schnell et al., 2021; Zhao et al., 2013). However, the atmospheric CO 2 has been continuously increasing in recent decades (Dayalu et al., 2020; Wang et al., 2010; Zhang et al., 2015).…”
Section: Resultsmentioning
confidence: 99%
“…China has already implemented various strategies, including the 11th Five Year Plan (2006–2010) as well as a number of pollution reduction and energy conservation measures since the 2008 Beijing Olympic Games, such as improving coal combustion efficiency, shutting down factories, and developing new fuels (Schnell et al., 2021; Zhao et al., 2013). However, the atmospheric CO 2 has been continuously increasing in recent decades (Dayalu et al., 2020; Wang et al., 2010; Zhang et al., 2015).…”
Section: Resultsmentioning
confidence: 99%
“…To address the urgency of climate change and explore the potential of further improving air quality via AEV deployment, our study considered a variety of decarbonization levels for electricity generation and includes more AEV types than Liang et al 11 or Schnell et al 16 Liang et al 11 estimated the air quality and health benefits of projected electric passenger vehicle penetration in 2030, given current policies, and found 17,456 (95% CI: 10,656-22,160) avoided annual premature deaths nationally due to reduced PM 2.5 and O 3 concentrations in China. We find that in our scenarios the avoided premature deaths due to an expansion of the AEV fleet including EVs, EMCs, HFCVs, and NGVs powered with over 90% decarbonized electricity could be as large as $329,000 persons (95% CI: 254,200-383,100).…”
Section: Discussionmentioning
confidence: 99%
“…We find that in our scenarios the avoided premature deaths due to an expansion of the AEV fleet including EVs, EMCs, HFCVs, and NGVs powered with over 90% decarbonized electricity could be as large as $329,000 persons (95% CI: 254,200-383,100). Schnell et al 16 found that the deployment of passenger and LDT EVs ameliorate several wintertime air pollution episodes, bring health benefits, and reduce CO 2 emissions when the marginal electricity generation is 50% emission-free. However, summer O 3 pollution is also detrimental to human health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S1 ( 60)). We estimate the increase in energy demand at EGUs by modeling the U.S. energy grid using an augmented version of the energy dispatch algorithm employed by (30,61). Emission changes at EGUs are computed at the CONUS level from which the changes occurring at EGUs within our study domain are selected.…”
Section: Air Quality Model Set-up and Ehdv Emission Scenariosmentioning
confidence: 99%